Sefer Meor’ot Zvi (The Book of the Trials and Tribulations of Zvi): Towards the Characteristics of the First Hebrew Novel - Yassif, Eli (MiKAN, 2022)
This early nineteenth century novel tells the story of the 17th century, self-proclaimed messiah Shabetai Zvi and the major events of his movement. It is a pioneering fictional from almost every aspect considered: style and language, narrative structure, characterization, literary imagery, historical conceptualization and ideology. The anonymous author, who wrote this book, presumably, in late 18th or early 19th century, made extensive use of historical sources from the time of Shabetai Zvi and his movement, to create a wholly revolutionary, novelistic, context and worldview. Ideologically, this is a typically marginal literary work, located between the traditional religious world and the new Haskalah (Enlightenment) worldview in Jewish life and culture. A very popular text, which went through many reprints during the 19th and early 20th centuries, it is a pioneering work of art which opened new horizons for modern Hebrew literature.